(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
Adaptive higher-order finite element methods (hp-FEM) are well known for their potential of exceptionally fast (exponential) convergence. However, most hp-FEM codes remain in an academic setting due to an extreme algorithmic complexity of hp-adaptivity algorithms. This paper aims at simplifying hp-adaptivity for H(curl)-conforming approximations by presenting a novel technique of arbitrary-level hanging nodes. The technique is described and it is demonstrated numerically that it makes adaptive hp-FEM more efficient compared to hp-FEM on regular meshes and meshes with one-level hanging nodes.